Validity of Ratings of Perceived Exertion in Patients with Type 2 Diabetes - Jessica L. Unick; Sarah Gaussoin; Judy Bahnson; Richard Crow; Jeff Curtis; Tina Killean; Judith G Regensteiner; Kerry J Stewart; Rena R Wing; John M Jakicic (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2014)
Purpose: To examine whether a subjective measure of moderate-intensity exercise (12-13 on Borg's ratings of perceived exertion scale; RPE) corresponds to the target heart rate for moderate-intensity exercise (40-59% heart rate reserve; %HRR) and to determine the characteristics of those for whom RPE does not appropriately estimate exercise intensity.  Methods: 3582 individuals with type 2 diabetes (age: 58.3±6.8 years; BMI: 35.9±5.9 kg/m2) underwent a maximal exercise test and minute-by-minute HR and RPE were recorded. Linear regression was used to determine the %HRR corresponding to an RPE of 12 and 13 for each individual.  Results: At an RPE of 12 or 13, 57% of participants fell within the target 40-59% HRR range, while 37% and 6% fell above and below this range, respectively. Participants with a %HRR ≥60% (above range) were more likely to be female (OR: 1.19; 95% CI: 1.01,1.40), African American (OR: 1.65; 95% CI: 1.35, 2.02) or Hispanic (OR: 1.57; 95% CI: 1.27, 1.95), have a higher BMI (OR: 1.03; 95% CI 1.01, 1.04) and HRmax (OR: 1.02; 95% CI: 1.01, 1.02), and lower fitness (OR: 0.90; 95% CI: 0.85, 0.94) and RPEmax (OR: 0.68; 95% CI: 0.63, 0.73), compared to those within the target 40-59%HRR range (p-values'<0.05).  Conclusions: RPE appropriately gauges exercise intensity in approximately half of overweight individuals with type 2 diabetes; however, more than one-third of participants were at an increased risk of exercising at a higher than prescribed intensity when using RPE. Future studies should continue to examine the characteristics of individuals for whom RPE appropriately estimates exercise intensity and for those whom it does not. Pubmed Link: https://www.ncbi.nlm.nih.gov/pubmed/25485308